SMART HOME APPS WITH VOICE USER INTERFACE - Bayu Faris Arkan; Marti Widya Sari; R. Hafid Hardyanto; Banu Santoso (JITEK (Jurnal Ilmiah Teknosains), 2022)
The development of the concept of Internet of Things (IoT) makes people excited about making devices that can control electrical devices remotely even when they are not at home. This system is known as a smart home. This smart home system controls electrical devices such as lights, fans, sockets and door locks through a smartphone application with the Android operating system that is connected to the internet. The Android application has a login security system so that not just anyone can control the device. To be able to control the device, a NodeMCU ESP-8266 microcontroller is needed which is already connected to the internet network as a data receiver through the Realtime Firebase database and a relay as a regulator of electric current from the plug to the device. Device control can use 2 modes, namely voice recognition mode and manual button mode. Voice recognition mode uses a special command code listed in the application in the Guide menu or guide. Every activity in controlling electrical devices will be recorded in the activity log and stored in Google Sheets, so that these activities can be monitored and can save electricity usage.